A time-domain method for hydroelasticity of very large floating structures in inhomogeneous sea conditions. (January 2018) - Wei, Wei; Fu, Shixiao; Moan, Torgeir; Song, Chunhui; Ren, Tongxin
Abstract: In this paper, a time-domain hydroelastic method for very large floating structures (VLFS′) in inhomogeneous waves is developed based on Cummins' equation. By discretizing the continuous VLFS into rigid modules connected by elastic beam elements, the inhomogeneous wave effect can be considered by adopting different wave spectra over different regions of the VLFS. In this method, the frequency-domain hydrodynamic coefficients, considering the hydrodynamic interactions between each floating module, are transformed into the time-domain hydroelastic model using Cummins' equation. Moreover, the time-domain wave excitation forces on the modules in different regions are solved using different wave spectra. The hydroelastic responses of a freely floating structure in inhomogeneous regular and irregular waves are investigated. The results show that the inhomogeneity of waves has a significant effect on the bending moments, shear forces and torsional moments of the structure, especially for a wave direction of 90°, in which larger forces may be induced compared with the homogeneous waves. Highlights: A discrete-modules-based time-domain hydroelasticity method for VLFS' is developed. The proposed method is validated against the traditional frequency 3D hydroelasticity method. Inhomogeneous wave effects to the hydroelastic responses of a freely floating VLFS are investigated. The inhomogeneity of waves should be considered for VLFS' to assure a safe design.